2013
DOI: 10.1177/2048872613504698
|View full text |Cite
|
Sign up to set email alerts
|

Patients with microvascular obstruction after primary percutaneous coronary intervention show a gp91phox (NOX2) mediated persistent oxidative stress after reperfusion

Abstract: Background: Persistent oxidative stress may play a key role in microvascular obstruction (MVO). We aimed at assessing the role of platelet gp91phox (NOX2), the catalytic subunit of NADPH oxidase in MVO. Methods: We enrolled 40 patients with ST-elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention within 12 h from symptoms onset, either with angiographic MVO (n=20) or good angiographic myocardial reperfusion (MR) (n=20). Angiographic MVO was defined as a final thrombolysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Nox2-derived ROS are up-regulated in peripheral blood of STEMI patients [ 8 ] but the interplay with platelet activation at coronary site is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Nox2-derived ROS are up-regulated in peripheral blood of STEMI patients [ 8 ] but the interplay with platelet activation at coronary site is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Reperfusion strategies, such as thrombolysis, angioplasty, and percutaneous coronary intervention (PCI), when applied expeditiously, and coronary artery bypass grafting (CABG) can restore coronary flow and limit myocardial infarct size (IS), and reperfusion per se can paradoxically trigger irreversible tissue injury, namely, ischemia-reperfusion injury (IRI) which is regarded as an important contributor to the unsuccessful recovery after reperfusion therapy [ 5 , 6 ]. The increased reactive oxygen species (ROS) production during reperfusion and the subsequently increased oxidative damage are regarded as a pivotal factor contributing to the pathogenesis of IRI [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress has also been linked to the development of microvascular obstruction. Speci cally, sustained levels of NOX2, the catalytic subunit of NADPH oxidase that is released by platelet activation, result in a vicious cycle of platelet aggregate stabilization and thrombus growth that contributes to CNR [21] . Huczek et al found that patients with higher platelet reactivity assessed by PFA-100 had a signi cantly higher percentage of angiographic NRP [22] .…”
Section: Discussionmentioning
confidence: 99%